(untitled) (Asian Journal of Pharmaceutics (AJP), 2022)
Background: Calcineurin inhibitors (CNIs) (Tacrolimus and cyclosporine [CSA]) are immunosuppressive drugs that are administrated to prevent liver rejection after liver transplantation. Their use has led to a reduced prevalence of acute rejection and improved transplant survival. However, their use is associated with many complications, these complications include hyperkalemia nephrotoxicity, hypertension (HTN), and new-onset diabetes mellitus (NODM). This study aimed to detect the incidence of CNIs complications in Egyptian patients after liver transplantation. Study Design: A retrospective evaluation with descriptive analysis study. Patients: All adults admitted for liver transplantation from 2008 to 2016 were included in this study. Setting: The study was conducted in the Liver Transplantation Unit, Ain Shams specialized hospital, Cairo, Egypt. Results: A total of 196 patients’ medical files were retrospectively reviewed to detect the incidence of CNIs complications. The tacrolimus group included 86 patients and the cyclosporin group included 92 patients. The prevalence of developing HTN was lower in the cyclosporin group as only 25% of patients developed HTN versus 40% in the tacrolimus group. The prevalence of NODM in the tacrolimus group was higher in the CSA group (33% vs. 16%). The prevalence of hyperkalemia was 52% and 28% in group tacrolimus and cyclosporin groups, respectively. The rate of nephrotoxicity in the tacrolimus group was 60% versus 48% in the cyclosporin group. Conclusions: These findings may help guide physicians in their choice of immunosuppression and underscore the need for long-term follow-up for blood sugar and potassium levels, blood pressure, and kidney function tests.